Great Canadian Lagerstätten 4. The Devonian Miguasha Biota (Québec): UNESCO World Heritage Site and a Time Capsule in the Early History of Vertebrates - Cloutier, Richard (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2013)
SUMMARY Over the past 170 years, the Late Devonian Miguasha biota from eastern Canada has yielded a diverse aquatic assemblage including 20 species of lower vertebrates (anaspids, osteostra-cans, placoderms, acanthodians, actinopterygians and sarcopterygians), a more limited invertebrate assemblage, and a continental component including plants, scorpions and millipedes. Originally interpreted as a freshwater lacustrine environment, recent paleontological, taphonomic, sedimentological and geochemical evidence corroborates a brackish estuarine setting. Over 18,000 fish specimens have been recovered showing various modes of fossilization, including uncompressed material and soft-tissue preservation. Most vertebrates are known from numerous, complete, articulated specimens. Exceptionally well-preserved larval and juvenile specimens have been identified for 14 out of the 20 species of fishes, allowing growth studies. Numerous horizons within the Escuminac Formation are now interpreted as either Konservat– or Konzentrat–Lagerstätten.